Glandular odontogenic cyst: A case report of an unusual lesion - Nandhini Gunasekaran; Rajkumar Krishnan; Rema Krishnan (Wolters Kluwer Medknow Publications, 2021)
Glandular odontogenic cyst (GOC) is a rare cyst occurring in the jaw bone having an uncertain and aggressive behavior with high recurrence rate. The diagnosis of this lesion is trying as it can be confused with other jaw cysts and malignant lesions. Treatment methods vary from conservative surgical treatment to jaw resection. This article presents a case of GOC mimicking radiographically as a lateral periodontal cyst.